2020
DOI: 10.1002/agj2.20075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertilizer management strategies on maize yield and nitrogen use efficiencies under different densities

Abstract: Rational plant density and fertilizer management are important practices to improve maize (Zea mays L.) yield and nutrient use efficiency. Previous research indicated that plant density and fertilization had positive interaction on maize yield and N utilization. The research studied on the interactive effects of slow‐released fertilizer (added amino acid polymer biological preparation) and density on maize yield and nitrogen use efficiencies (NUEs). A 2‐yr field experiment with varieties Suyu29 (SY29) or Suyu3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 47 publications
1
9
0
Order By: Relevance
“…In addition to differences among maize hybrids for plant height, soil compaction also restricted the plants from gaining height. These results are in accordance with the earlier findings of Li et al (2020), who reported that various hybrids responded differently in plant height.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition to differences among maize hybrids for plant height, soil compaction also restricted the plants from gaining height. These results are in accordance with the earlier findings of Li et al (2020), who reported that various hybrids responded differently in plant height.…”
Section: Discussionsupporting
confidence: 93%
“…As the crop roots penetrate upto 12 cm deep in search of nutrients and water at the tasseling stage, increasing bulk density will affect this intake by roots, thereby causing a delay in days to taselling. Anjum et al (2018)and Li et al (2020) also reported a change in days to tasseling of maize with different bulk densities of soil. Wang et al (2022) also reported a negative correlation between hybrid maize yield with the increase in soil compactness.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This compound fertilizer was added to an amino acid polymer biological preparation which had negative charges with strong adsorption. The biological preparation could form amino acid, which acts as a biostimulant after metabolism [ 25 ]. Five treatments were set at two sites, including F0 (no fertilization), 3 optimized fertilization practices (F1, F2, and F3), and F4 (control treatment).…”
Section: Methodsmentioning
confidence: 99%
“…According to Shao et al ( 2018 ), root length and root number per plant decrease significantly as planting density increases. The increase in planting density not only inhibits the growth, quantity, and quality of maize roots but also reduces nutrient absorption and translocation in maize (Li et al, 2020 ; Gao et al, 2021 ). Therefore, enhancing root physiological characteristics and nutrient absorption capacity in high-density planting for optimal maize growth and high yield has become a significant problem in maize production.…”
Section: Introductionmentioning
confidence: 99%